2022
DOI: 10.1145/3508478
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Analysis on the Impact of Contextual Information on Point-of-Interest Recommendation

Abstract: As the popularity of Location-based Social Networks (LBSNs) increases, designing accurate models for Point-of-Interest (POI) recommendation receives more attention. POI recommendation is often performed by incorporating contextual information into previously designed recommendation algorithms. Some of the major contextual information that has been considered in POI recommendation are the location attributes (i.e., exact coordinates of a location, category, and check-in time), the user attributes (i.e., comment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 91 publications
0
8
0
Order By: Relevance
“…Our future plans include the incorporation of deep learning, graph-based, sequential, and sessions-based models as proposed in works like [1,9]. These models can integrate various contextual components like geographical, temporal, social, and categorical relevance scores using fusion rules such as product or sum [8,12], forming a unified preference score [10,13,16]. Contextual information, denoted by 𝑐 𝑖 , can be infused using a polynomial regression model 𝑟𝑒𝑐 𝑢,𝑝 " Λ ¨C `Λpair ¨Cpair `𝜆123 𝑐 1 𝑐 2 𝑐 3 (1) where:…”
Section: Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our future plans include the incorporation of deep learning, graph-based, sequential, and sessions-based models as proposed in works like [1,9]. These models can integrate various contextual components like geographical, temporal, social, and categorical relevance scores using fusion rules such as product or sum [8,12], forming a unified preference score [10,13,16]. Contextual information, denoted by 𝑐 𝑖 , can be infused using a polynomial regression model 𝑟𝑒𝑐 𝑢,𝑝 " Λ ¨C `Λpair ¨Cpair `𝜆123 𝑐 1 𝑐 2 𝑐 3 (1) where:…”
Section: Modelsmentioning
confidence: 99%
“…Other types of context may include social ties, the category of POIs, comments on POIs, etc. Previous research works such as [12] have shown the way incorporating these rich contexts information have a significant impact on the performance of POI recommendation models. Therefore, in recent years, there has been a growth in the demand for specialized recommendation algorithms and methodologies that can incorporate and fuse contextual information into the POI recommendation process [24]; arXiv:2306.11395v1 [cs.IR] 20 Jun 2023…”
Section: Introductionmentioning
confidence: 99%
“…Research shows that contextual information plays an important role in location recommendation tasks [28] and thus context-based location recommendation models focusing on point-of-interest (POI) are gradually developed. For example GT-HAN [21] used three factors (the geo-influence of POIs, the geo-susceptibility of POIs, and the distance between POIs) to model the geographical co-influence between two POIs, and applied attention network to integrate those features for location recommendation.…”
Section: Next Location Recommendationmentioning
confidence: 99%
“…Therefore, we believe that preference consis- tency between users, rather than friendship itself, determines the behavior similarity between users. -Third, although various embedding methods with auxiliary information have been proposed to learn the representations that capture users' sequential movements [47,27,38,37], their ability to learn complex patterns, especially hierarchical structures, is limited [9,28]. Meanwhile, contextual information from distinctive sources is assembled and mapped to a uniform space for representation learning [2,40], which limits the model's capacity to exploit the fine-grained intrinsic interactions between contexts for better performance.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, POI data have the advantages of simple acquisition and convenient processing, meaning that POI data are widely used in geographical research. At present, the research on POI mainly focuses on a recommendation model [19][20][21] and urban functional zoning [22], and the research on POI itself mainly focuses on automatic classification [23] and classification accuracy by using machine learning. Nak introduced POI into eye-tracking data analysis [24], making the research scope of POI broader.…”
Section: Introductionmentioning
confidence: 99%